(untitled) (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
Abstract The paper deepens the understanding of transference in psychosis by articulating theory and clinical practice based on Freud, Lacan, Bion, Soler, and Zenoni. Through a critical literature review, it discusses transfer mechanisms and the particularities of the therapeutic bond in psychotic structures. Transference in psychosis emerges as a vector of subjectivation that requires from the analyst an ethical and containing stance. The author argues that handling transference demands balance between silence and intervention, positioning the analyst as “the secretary of the mad.” It concludes that transference, rather than an obstacle, is a privileged space of symbolization and subjective reconstruction in the clinical field of psychosis.